Celastrol Attenuates RANKL-Induced Osteoclastogenesis in vitro and Reduces Titanium Particle-Induced Osteolysis and Ovariectomy-Induced Bone Loss in vivo - Xu, Qiang; Chen, Guiping; Xu, Huaen; Xia, Guoming; Zhu, Meisong; Zhan, Haibo; Zhang, Bin; Dai, Min; Fan, Hongxian; Liu, Xuqiang (Frontiers in Pharmacology, 2021)
Excessive bone resorption by osteoclasts plays an important role in osteoclast-related diseases involving periprosthetic osteolysis and osteoporosis. Osteolysis in a titanium particle-induced calvarial model and bone loss in an ovariectomized mice model occurred similarly to those in humans; thus, these models can be used to evaluate potential therapies for aseptic prosthetic loosening and osteoporosis. Celastrol, derived from the roots of the genus Tripterygium, has been well-studied for its potential anti-inflammatory and anti-cancer pharmacological properties. However, the mechanisms involving bone metabolism by which celastrol inhibits osteoclastogenesis are not yet fully understood. We demonstrated that celastrol inhibited the receptor activator of nuclear factor κB ligand-induced osteoclastogenesis and the bone resorptive function of osteoclasts in vitro by inhibiting the activation of transforming growth factor β-activated kinase 1-mediated NF-κB and mitogen-activated protein kinase signaling pathways and downregulating osteoclastogenesis marker-related genes. Furthermore, celastrol played a protective role in both titanium particle-induced osteolysis calvarial and murine ovariectomy-induced bone loss models in vivo. Collectively, our results suggested that celastrol is promising for the prevention of aseptic prosthetic loosening and osteoporosis in the treatment of osteolytic diseases caused by disrupted osteoclast formation and function.